Effect of epithelial-specific MyD88 signaling pathway on airway inflammatory response to organic dust exposure. Issue 1 (31st December 2023) - Johnson, Amber N.; Dickinson, John; Nelson, Amy; Gaurav, Rohit; Kudrna, Katrina; Evans, Scott E.; Janike, Katherine; Wyatt, Todd A.; Poole, Jill A.
Abstract: The Toll-like receptor (TLR) adaptor protein MyD88 is integral to airway inflammatory response to microbial-enriched organic dust extract (ODE) exposures. ODE-induced airway neutrophil influx and release of pro-inflammatory cytokines was essentially abrogated in global MyD88-deficient mice, yet these mice demonstrate an increase in airway epithelial cell mucin expression. To further elucidate the role of MyD88-dependent responses specific to lung airway epithelial cells in response to ODE in vivo, the surfactant protein C protein (SPC) Cre + embryologic expressing airway epithelial cells floxed for MyD88 to disrupt MyD88 signaling were utilized. The inducible club cell secretory protein (CCSP) Cre +, MyD88 floxed, were also developed. Using an established protocol, mice were intranasally instilled with ODE or saline once or daily up to 3 weeks. Mice with MyD88-deficient SPC + lung epithelial cells exhibited decreased neutrophil influx following ODE exposure once and repetitively for 1 week without modulation of classic pro-inflammatory mediators including tumor necrosis factor (TNF)-α, interleukin (IL)-6, and neutrophil chemoattractants. This protective response was lost after 3 weeks of repetitive exposure. ODE-induced Muc5ac mucin expression at 1 week was also reduced in MyD88-deficient SPC + cells. Acute ODE-induced IL-33 was reduced in MyD88-deficient SPC + cells whereas serum IgE levels were increased at one week. In contrast, mice with inducible MyD88-deficient CCSP + airway epithelial cells demonstrated no significant difference in experimental indices following ODE exposure. Collectively, these findings suggest that MyD88-dependent signaling targeted to all airway epithelial cells plays an important role in mediating neutrophil influx and mucin production in response to acute organic dust exposures.